Effectiveness of climate information services in Sub-Saharan Africa’s agricultural sector: a systematic review of what works, what doesn’t work, and why - Khatibu, Salma; Ngowi, Edwin (Frontiers in Climate, 2025)
IntroductionThis study examines effectiveness of Climate Information Services (CIS) in improving agricultural resilience in Sub-Saharan Africa (SSA), where their potential remains underutilized despite their significance in climate change adaptation.MethodsEmploying PRISMA methodology, we systematically reviewed 53 peer-reviewed articles published between 2010-2023, using inferential statistical analysis to assess factors influencing CIS adoption and effectiveness.ResultsThe results reveal that “What Works” are participatory models like Participatory Integrated Climate Services for Agriculture (PICSA), which significantly enhance adoption rates, because they involve local communities in climate service design. “What Does not Work” are top-down models that do not consider local contexts, leading to low adoption. Barriers to CIS success include poor digital infrastructure, low literacy rates, and gender biases, hindering effective use.Discussion“Why” these approaches fail is due to disconnect between services offered and actual needs of farmers, with a lack of trust in externally provided information. In conclusion, CIS can significantly contribute to agricultural resilience if designed to be inclusive, context-specific, and participatory. The study recommends scaling up participatory models, enhancing digital infrastructure, and integrating CIS into national agricultural policies to improve accessibility, usability, and farmer engagement, thereby strengthening climate adaptation and resilience in SSA.